Preparation for the care of children with chronic diseases: the perception of caregivers - Rebecca Camurça Torquato; Giselle Pereira Rovere; Mardênia Gomes Vasconcelos Pitombeira; Aline de Souza Pereira; Luciana Kelly Ximenes dos Santos (Universidade Federal do Ceará, 2020)
Objective: to describe the caregivers' perception of preparation to care for children with chronic diseases. Methods: qualitative research, carried out with nine caregivers in a home transition unit in a tertiary hospital. Semi-structured interviews were used to obtain the data, and the content analysis technique was used to describe the results. Results: with the qualitative material analysis process, the main perceptions of the reported care were obtained: Knowing the Care Unit; Training, learning and guidance and Difficulties faced. Conclusion: the preparation for the care of children with chronic diseases is complex and was perceived as a fundamental step towards leaving hospital, requiring from these caregivers donation and effort to face this process.